MATHEMATICAL MODEL OF PROBLEM OF PLANNING OF TECHNOLOGICAL PROCESSES OF PRE-FLIGHT PREPARATION OF AIRPLANES - Масловський, Б. Г. (Science-based technologies, 2015)
The problem of management preparation of aircrafts is certain to flight on the movable (mobile) air fields, that requires application of the special going near planning of technological processes of pre-flight preparation. The aim of the article is a decision of problem of planning of technological processes of preparation of aircrafts to flight, as parts of general problem of management pre-flight preparation of aircrafts. The mathematical model of decision of problem of planning of technological processes of preparation of aircrafts is presented to flight, determination of criteria of her optimality and limitations for a decision. Maintenance of technological chart of pre-flight preparation of every aircraft is given as a complex of associate works, that is presented by the set of qualificatory plurals and sizes. Certain initial data, and also resultants are variables the values of that are able to describe decision of problem of planning of technological processes of preparation of aircrafts to flight. The algorithm of bringing an initial mathematical model over of the put problem is given to the canonical form with determination of limitation as certain requirements.